Characterization of HIV-1 Proviral Latency Induced Through APOBEC3 Mutagenesis and Reverse Transcriptase Error - Greig, Matthew (Université d'Ottawa / University of Ottawa, 2020)
Human Immunodeficiency Virus 1 (HIV-1) is a lentivirus that forms persistent latently infected reservoirs that are the remaining major hurdle for current HIV-1 treatments. APOBEC3 (A3) proteins are intrinsic retroviral restriction factors that introduce GA mutations during reverse transcription, while Reverse Transcriptase (RT) introduces on average 2-3 mutations every reverse transcription cycle due to a lack of proofreading ability. The goal of this research is to characterize the infectivity and activation of mutated HIV-1 viruses that display reduced transcription upon infection, viruses that we term latency prone viruses (LPVs). We hypothesize that GA transition mutations in the HIV-1 Long Terminal Repeat (LTR) region of the LPVs introduced through Reverse Transcriptase and low levels of A3 protein activity can create HIV-1 sequences that display a reversible, latency-like phenotype. Variable levels of transcription and promoter activation were seen among the LPVs when tested against four classes of Latency Reversing Agents (LRAs). Subsequently, three tested LPVs demonstrated an initial latency-like phenotype before rebounding in infectivity. This project demonstrates for the first time that HIV-1 latency is not simply a byproduct of the infection timing and cellular conditions, but that replication-competent HIV-1 latent viruses can also be created through sublethal mutagenesis of their viral promoter sequence introduced through A3 and RT exposure. The characterization of the complete mechanism of HIV-1 latency induction, maintenance, and reversal is critical in the development of sterilizing and functional cures for HIV-1 infection.
Keywords: HIV-1; Reverse Transcriptase; APOBEC3; HIV-1 Latency